2009
DOI: 10.1093/humrep/dep302
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole combined with norethisterone acetate compared with norethisterone acetate alone in the treatment of pain symptoms caused by endometriosis

Abstract: The combination drug regimen was more effective in reducing pain and deep dyspareunia than norethisterone acetate; however, letrozole caused a higher incidence of adverse effects, cost more and did not improve patients' satisfaction or influence recurrence of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 45 publications
1
72
0
3
Order By: Relevance
“…6,10,12,13,15,[17][18][19][20][22][23][24][26][27][28]31,32 The main results of these studies are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,10,12,13,15,[17][18][19][20][22][23][24][26][27][28]31,32 The main results of these studies are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Patients are advised to mark the position that reflects the degree of pain, with 0 being no pain and 10 or 100 considered the worst pain experienced. 15,27 One way to reduce the painful symptoms in patients with endometriosis is to use conventional treatment including surgery and/or medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the patient's compliance of the combined therapy is lower due to the higher incidence of unwanted side effects experienced by the patients such as joint pain and muscle aches. The recurrence of pain related symptoms was reported to be equal in both drug regimens, where the patients experienced pain symptoms within three months after ceasing treatment [27]. Another study reported by Abushahin et al showed that there was improvement of pain related symptoms after six months of Letrozole treatment combining with oral contraceptive pills.…”
Section: Pain In Endometriosismentioning
confidence: 95%
“…Letrozole and Norethisterone acetate compared with progestin monotherapy [27]. However, the patient's compliance of the combined therapy is lower due to the higher incidence of unwanted side effects experienced by the patients such as joint pain and muscle aches.…”
Section: Pain In Endometriosismentioning
confidence: 99%